Screening of Novel Materials for Biodiesel Production Through the Esterification of Oleic Acid - Matkovic, Silvana Raquel; Nilsson, Juliet Fernanda; Fait, María Elisa; Morcelle del Valle, Susana Raquel; Briand, Laura Estefania
The present contribution screens the specific activity of various inorganic and enzymatic based materials in the esterification of oleic acid that is typically used as a test reaction for the production of biodiesel from high free fatty acid feedstocks. The inorganic materials investigated in this contribution are bulk fosfotungstic heteropoly acid of the Wells Dawson structure H6P2W18O62.nH2O (HPA), as well as dispersed on titanium dioxide 18 % w/w H6P2W18O62/TiO2 and the insoluble cesium salt of the Wells Dawson heteropoly anion Cs2H4P2W18O62. Additionally, the commercial biocatalyst Novozym® 435 (immobilized lipase B of Candida antarctica) and a self-supported lipase of vegetable origin obtained from the latex Araujia sericifera (ASL) were studied among the materials of enzymatic nature. The density and accessibility of Brønsted acid sites have a key role in the specific activity of the fosfotungstic based heteropoly compounds. The HPA dispersed over an oxide support catalyzed the esterification of the fatty acid in a heterogeneous fashion with the highest activity (6.4 μmol mg−1 h−1 at 85 °C) among the inorganic materials. In contrast, the enzymatic materials are more active at lower temperature than the inorganic ones. Particularly, ASL catalyzed the homogenous methanolysis with the highest specific activity (30.7 μmol mg−1 h−1 at 40 °C) at the lowest temperature among the materials assayed. Fil: Matkovic, Silvana Raquel. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata. Centro de Investigación y Desarrollo en Ciencias Aplicadas "Dr. Jorge J. Ronco". Universidad Nacional de la Plata. Facultad de Ciencias Exactas. Centro de Investigación y Desarrollo en Ciencias Aplicadas; Argentina Fil: Nilsson, Juliet Fernanda. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata. Instituto de Biotecnología y Biología Molecular. Universidad Nacional de La Plata. Facultad de Ciencias Exactas. Instituto de ...